IDENTIFICATION OF STUDENTS METACOGNITION LEVELS IN PROBLEM-SOLVING AND MATHEMATICAL LITERACY - Maya Trisnani; Widodo Winarso (CAHAYA PENDIDIKAN, 2019)
Metacognition is knowledge and awareness about the process of cognition or learning about the mind and how it works. Solving mathematical problems requires the involvement of metacognition. This study aims to obtain the results of identification of students' level of metacognition in problem-solving and the level of metacognition of students in mathematical literacy on social arithmetic material. This research was conducted at SMP Negeri 3 Palimanan. This type of research is qualitative research. The subjects of this study were students of class VII C Middle School 3 Palimanan. Data collected by test and interview methods. Data were analyzed using data reduction, data presentation, and concluding. The results of this study indicate that the level of metacognition of students in solving mathematical problems and mathematical literacy has mixed results. In solving mathematical problems, students who have high learning outcomes are at the level of Reflective Use metacognition, students who have learning outcomes are at the Strategic Use metacognition level, and students who have low learning outcomes are at the Tacit Use metacognition level. Meanwhile, the level of student metacognition in mathematics literacy is not much different from solving mathematical problems. Students who have high learning outcomes are at the Reflective Use metacognition level, students who have learning outcomes are at the Strategic Use metacognition level, and students who have low learning outcomes are at the Aware Use metacognition level. Overall the level of metacognition of students both in solving mathematical problems and in mathematics literacy is at the level of Strategic Use metacognition